Cytomegalovirus pre‐emptive therapy after hematopoietic stem cell transplantation in the era of real‐time quantitative PCR: comparison with recipients of solid organ transplants. Issue 3 (9th June 2016) - Panagou, E.; Zakout, G.; Keshani, J.; Smith, C.; Irish, D.; Mackinnon, S.; Kottaridis, P.; Fielding, A.; Griffiths, P.D.
Abstract: Background: Cytomegalovirus (CMV) continues to be an important complication of hematopoietic stem cell transplantation and solid organ transplantation. Methods: In this study, 314 patients who underwent hematopoietic stem cell transplantation between January 2003 and October 2011 were tested serially for CMV DNA by real‐time quantitative polymerase chain reaction (qPCR) for 90 days post transplantation. Patients with CMV viremia >3000 genomes/mL (equivalent to 2520 IU/mL) received pre‐emptive therapy and were compared with previously published data from solid organ transplant (SOT) patients monitored and treated in exactly the same way. Results: After stem cell transplant (SCT), 48% of patients developed at least 1 episode of viremia. The median duration of a viremic episode was 25 days and the peak viral load (VL) was 4784 genomes/mL whole blood (equivalent to 4019 IU/mL). The data demonstrated that recipients with positive CMV serostatus were at increased risk of developing viremia, with 0% of donor‐negative/recipient‐negative (D−R−), 3.7% of D+R−, 79.5% of D−R+, and 74.2% of D+R+ groups developing viremia over follow‐up (adjusted hazard ratio for D+R− vs. D+R+ group 0.03; 95% confidence interval 0.004, 0.18; P = 0.0013). In contrast with SOT patients, where 58/74 (78%) D+R− patients had viremia, a low risk of CMV infection was seen after stem cell transplantation (1/27; 3.7%). Conclusion: As both groups of patients, the previously published SOT patients and the present hematopoietic SCT patients, were monitored using the same protocol and qPCR assay with pre‐emptive therapy administered at the same VL cutoffs, the distinct differences seen cannot be explained by differences in testing or management and thus emphasize distinct aspects of the natural history of CMV infection post transplant in these 2 patient groups.